Antidiabetic effects of Andrographis paniculata supplementation on biochemical parameters, inflammatory responses, and oxidative stress in canine diabetes - Suemanotham, Namphung; Phochantachinda, Sataporn; Chatchaisak, Duangthip; Sakcamduang, Walasinee; Chansawhang, Anchana; Pitchakarn, Pornsiri; Chantong, Boonrat (Frontiers in Pharmacology, 2023)
Diabetes mellitus is a common endocrine disorder that causes hyperglycemia in dogs. Persistent hyperglycemia can induce inflammation and oxidative stress. This study aimed to investigate the effects of Andrographis paniculata (Burm.f.) Nees [Acanthaceae] (A. paniculata) on blood glucose, inflammation, and oxidative stress in canine diabetes. A total of 41 client-owned dogs (23 diabetic and 18 clinically healthy) were included in this double-blind, placebo-controlled trial. The diabetic dogs were further divided into two treatments protocols: 1) received A. paniculata extract capsules (50 mg/kg/day; n = 6) or received placebo for 90 days (n = 7); 2) received A. paniculata extract capsules (100 mg/kg/day; n = 6) or received a placebo for 180 days (n = 4). Blood and urine samples were collected every month. No significant differences in fasting blood glucose, fructosamine, interleukin-6, tumor necrosis factor-alpha, superoxide dismutase, and malondialdehyde levels were observed between the treatment and placebo groups (P > 0.05). The levels of alanine aminotransferase, alkaline phosphatase, blood urea nitrogen, and creatinine were stable in the treatment groups. The blood glucose levels and concentrations of inflammatory and oxidative stress markers in the client-owned diabetic dogs were not altered by A. paniculata supplementation. Furthermore, treatment with this extract did not have any adverse effects on the animals. Nonetheless, the effects of A. paniculata on canine diabetes must be appropriately evaluated using a proteomic approach and involving a wider variety of protein markers.